2021
DOI: 10.1039/d1tc03191k
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced polarization in epitaxially strained monoclinic potassium niobate for lead-free electromechanical applications

Abstract: To further our understanding of how complex anisotropic structure-property relationships may be rationalized by their local atomic arrangements in ferroelectric materials, using the newly-found metastable monoclinic P m phase of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 66 publications
0
11
0
Order By: Relevance
“…It has been previously shown that for the pristine KNO system, K contributes minimally to the total P s while the major contribution comes from the NbO 6 octahedrons. [ 39,40 ] This suppression of the polarization response of K reflects the strong ionic interactions between K and O ions. [ 39 ]…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been previously shown that for the pristine KNO system, K contributes minimally to the total P s while the major contribution comes from the NbO 6 octahedrons. [ 39,40 ] This suppression of the polarization response of K reflects the strong ionic interactions between K and O ions. [ 39 ]…”
Section: Resultsmentioning
confidence: 99%
“…As evident from Figure 2, although the contribution of NbO 6 octahedrons to P s is dominant and well‐understood (i.e., via intra‐octahedral tilting mechanism), [ 39,40,46 ] the preferred use of P̂$\widehat{P}$ is palpable for the enhanced P s in for example, K 1 − x Li x NbO 3 alloys.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations